2020
DOI: 10.3389/fcell.2020.592048
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of LMP10 Attenuates Diet-Induced Atherosclerosis by Inhibiting Macrophage Polarization and Inflammation in Apolipoprotein E Deficient Mice

Abstract: Macrophage polarization and inflammation are key factors for the onset and progression of atherosclerosis. The immunoproteasome complex consists of three inducible catalytic subunits (LMP2, LMP10, and LMP7) that play a critical role in the regulation of these risk factors. We recently demonstrated that the LMP7 subunit promotes dietinduced atherosclerosis via inhibition of MERTK-mediated efferocytosis. Here, we explored the role of another subunit of LMP10 in the disease process, using ApoE knockout (ko) mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The roles of IL-6 in macrophages polarization are complex and various. In some particular conditions, IL-6 was regarded as pro-inflammatory M1 signature marker [56][57][58]. However, in other conditions IL-6 was expressed by M2 macrophages, such as the increased production of IL-6 by M2 macrophages which were induced by heparanase enzyme highly expressed pancreatic carcinoma cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of IL-6 in macrophages polarization are complex and various. In some particular conditions, IL-6 was regarded as pro-inflammatory M1 signature marker [56][57][58]. However, in other conditions IL-6 was expressed by M2 macrophages, such as the increased production of IL-6 by M2 macrophages which were induced by heparanase enzyme highly expressed pancreatic carcinoma cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages can be divided into M1 or M2 type, depending on the polarization state, all of which were derived from monocytes [50]. Recent studies showed that M2 macrophages could clear dying cells and debris and secrete antiinflammatory factors, which can attenuate the formation of AS plaques [51]. Our results showed that the ZBTB20 knockdown increased the M2 macrophage polarization but decreased the M1 macrophage polarization, implying that the ZBTB20 knockdown may attenuate AS by activating M2 macrophages.…”
mentioning
confidence: 57%
“…Previous studies have demonstrated the important role of macrophage polarization toward an M1/M2 subtype in atherosclerosis. For example, it was shown that LMP10 ablation inhibited macrophage polarization toward the proinflammatory M1 subtype 26 . HOXA5 was reported to promote adipose macrophages switching toward M2 phenotypes and attenuate chronic inflammation 19,20 .…”
Section: Discussionmentioning
confidence: 99%